Duration of Zidovudine Consumption Correlates with Anemia in People Living with HIV - Danis Pertiwi; Muchlis Achsan Udji Sofro; Tri Indah Winarni; Ari Natalia Probandari (Sanata Dharma University, 2023)
Anemia is the most common hematological disorder associated with Human Immunodeficiency Virus (HIV). WHO recommends zidovudine (AZT) as one of the first-line drugs for this infection. It is important to note that the drug has the adverse effect of causing anemia. Therefore, this study correlates AZT consumption duration and the incidence of anemia in HIV-infected individuals. This cross-sectional study was conducted at health service facilities using 213 participants. The data were obtained from medical records, and the assessed parameter was hemoglobin (Hb) level after less or more than a year of zidovudine administration. Furthermore, they were analyzed using a Pearson’s coefficient contingency test (p0.05) to evaluate the correlation between groups with and without anemia at each period of drug administration. The results showed a significant correlation (p0.05) between sex and age with anemia incidence in HIV patients administered AZT. The duration of this drug intake in HIV-infected individuals was correlated with anemia (p= 0.024; OR=0.369). This indicates the use of AZT for at least one year may be a protective factor for the incidence of anemia in patients with HIV compared to the group consuming this drug for less than one year.